Efficacy comparison of five antidepressants in treating anxiety and depression in cancer and non-cancer patients - Zhao, Kuan; Wang, Youyang; Liu, Qun; Yu, Ze; Feng, Wei (Frontiers in Neuroscience, 2024)
IntroductionCancer patients have a heightened susceptibility to anxiety and depressive disorders, which significantly impact the effectiveness of cancer treatments and long-term quality of life. This study aimed to compare the efficacy of different antidepressants in cancer and non-cancer patients.MethodsA total of 610 patients diagnosed with depressive episodes and/or anxiety disorders were retrospectively included and divided into a cancer group and a non-cancer control group. Antidepressants used included escitalopram, duloxetine, sertraline, venlafaxine, and vortioxetine, combined with trazodone or not. The Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder Questionnaire-7 (GAD-7) scores were used to evaluate the efficacy after 4 weeks and 8 weeks of systematic antidepressants treatment.ResultsCompared to the non-cancer group, the cancer group had higher proportions of females, older individuals, and patients with poor sleep quality, while reporting fewer somatic symptoms at baseline (all p < 0.05). PHQ-9 and GAD-7 scores in cancer patients treated with antidepressants were significantly lower than baseline at week 4 and week 8 (all p < 0.05). The sertraline group demonstrated significantly less improvement in GAD-7 scores at week 4 and in both GAD-7 and PHQ-9 scores at week 8 compared to the escitalopram group, while duloxetine, venlafaxine, and vortioxetine showed comparable efficacy to escitalopram. Antidepressants combined with trazodone showed significant improvement in PHQ-9 scores at week 4 compared to those without trazodone. The gynecological cancer group showed significantly more improvement in GAD-7 and PHQ-9 scores at week 4 and 8 compared to breast cancer patients.ConclusionAntidepressant treatment in cancer patients with anxiety and depression is as effective as in non-cancer patients. The efficacy of escitalopram is comparable to duloxetine, venlafaxine, and vortioxetine, all of which outperformed sertraline in cancer patients.